2015
DOI: 10.3329/jafmc.v10i1.22904
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic role of Ultrasonography in acute appendicitis

Abstract: Introduction: Abdominal Ultrasonography (USG) is the most commonly used method for diagnosing acute appendicitis the most common surgical cause of acute abdomen. In this study, we observed the reliability of USG for diagnosing acute appendicitis. Objectives:To evaluate the role of ultrasonography in the diagnosis of acute appendicitis. Methods:In this study, we performed abdominal USG of 100 patients admitted with lower right abdominal pain and diagnosed as acute surgical abdomen according to the physical exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Islam et al . [ 9 ] found acute appendicitis to be a common indication for emergency abdominal surgery. Arora et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Islam et al . [ 9 ] found acute appendicitis to be a common indication for emergency abdominal surgery. Arora et al .…”
Section: Discussionmentioning
confidence: 99%
“…This reflects that in acute abdomen clinical judgment is accurate with imaging and other laboratory investigations being supplementary. Islam et al ,[ 9 ] concluded that proper clinical assessment is the main stay of diagnosis in acute appendicitis. According to Gans et al ,[ 11 ] diagnostic accuracy of medical history and physical examination alone was insufficient to reach a correct diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Procedure related outcomes were inspiring 25 . Duration varies 30-120 minutes, mean 70 minutes, suggesting that it is not a time consuming procedure.…”
Section: Discussionmentioning
confidence: 99%